The renaissance of the city as a cluster of innovation - Jerome S. Engel; Jasmina Berbegal-Mirabent; Josep M. Piqué (Cogent Business & Management, 2018)
The first part of the twenty-first century has witnessed a rebirth of “the City” as an engine of innovation. This renaissance has been an organic response to technological and societal pressures, opportunities, and norms. This is a sharp reversal from the latter half of the twentieth century, which saw the decay and erosion of the City as a place of economic value creation. In spite of the best efforts of governments and city planners, suburbanization, first of residences, and then industry, led to a hollowing out than in some areas decimated urban life. What lessons can we learn from the emergent reversal of this trend? We explore in depth the examples of San Francisco, Austin (Texas), and London to discover lessons that may be broadly adopted.
Keywords: 650